A Case Study On Hong Leong Bank Berhad In Malaysia - Lee, Kim Lain (2006)
This research was conducted to study the customers' expectations and customers' perceptions (Gap 5) towards the internet banking service quality in HLBB by using the 17 internet banking service quality dimensions developed by Jun and Chai in 2001.